2022
DOI: 10.3390/nano12030426
|View full text |Cite
|
Sign up to set email alerts
|

Green-Synthesized Silver Nanoparticle–Assisted Radiofrequency Ablation for Improved Thermal Treatment Distribution

Abstract: Thermal ablation therapy is known as an advantageous alternative to surgery allowing the treatment of multiple tumors located in hard-to-reach locations or treating patients with medical conditions that are not compatible with surgery. Appropriate heat propagation and precise control over the heat propagation is considered a weak point of thermal ablation therapy. In this work, silver nanoparticles (AgNPs) are used to improve the heat propagation properties during the thermal ablation procedure. Green-synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…53 Currently, diverse metallic biomaterials, including Au-, Ag-, and Fe-based nanoparticles, have been reported to enhance the conversion of RF current to heat to achieve better RFA treatment outcomes. 46,48,54 Among them, gold nanoparticles have been reported to be able to increase RFA heating via the Joule heating principle, although this is still under debate. In a recent work by Tudor Mocan et al, it was uncovered that swine livers with percutaneous injection of PEG-coated gold nanoparticles through the electrode channel during RFA treatment showed a large coagulation zone volume as determined by using contrastenhanced ultrasound (CEUS).…”
Section: Metallic Biomaterial-assisted Rfamentioning
confidence: 99%
“…53 Currently, diverse metallic biomaterials, including Au-, Ag-, and Fe-based nanoparticles, have been reported to enhance the conversion of RF current to heat to achieve better RFA treatment outcomes. 46,48,54 Among them, gold nanoparticles have been reported to be able to increase RFA heating via the Joule heating principle, although this is still under debate. In a recent work by Tudor Mocan et al, it was uncovered that swine livers with percutaneous injection of PEG-coated gold nanoparticles through the electrode channel during RFA treatment showed a large coagulation zone volume as determined by using contrastenhanced ultrasound (CEUS).…”
Section: Metallic Biomaterial-assisted Rfamentioning
confidence: 99%
“…They are currently synthesized in many forms to catalyse reactions, protein separation, polymer preparation, sensor technology, optoelectronic recording media and heat propagating in thermal ablation therapy [31][32][33][34][35] . Nowadays, various disease imaging systems like magnetic resonance imaging, positron emission tomography, surface-enhanced Raman spectroscopy (SERS) and optical imaging are in use based on the magnetic property of NPs 36 . Wei et al in 2015 opined that weak interaction with AgNPs causes oscillation of conduction band electrons of AgNPs, and thereby, photon energy changes into thermal energy so that the SERS effect can be tamed to develop photothermal and thermolytic laser therapies 37 .…”
Section: Introductionmentioning
confidence: 99%
“…RFA provides a treatment that combines the miniaturization of the applicator and its tip electrodes with the localization of the bio-heating process in the surrounding tissue [ 11 ], as well as allowing the ablation of large volumes. Recent studies, in addition, have shown how the use of gold [ 12 ] and silver [ 13 ] nanoparticles might significantly expand the treated area. For example, Ashikbayeva et al reported a 102% increase in the ablated surface area when using green-synthesized Ag nanoparticles in an agarose gel, and a 72% increase when using agarose only.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ashikbayeva et al reported a 102% increase in the ablated surface area when using green-synthesized Ag nanoparticles in an agarose gel, and a 72% increase when using agarose only. Agarose gel is widely used in biomedicine material; it has biocompatible, antimicrobial characteristics, and demonstrates good heating performance in terms of temperature, heat distribution and the short time it takes to reach cytotoxic temperature ranges [ 13 ]. Overall, RFA allows a rapid (30–120 s) treatment, capable of reaching cytotoxic (>42 °C) and instantaneous cell mortality (>60 °C) temperature values [ 14 ] within a few seconds from the start.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation